2019
DOI: 10.1002/jbmr.3951
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Cells Down-Regulate Adiponectin in Bone Marrow Adipocytes Via TNF-Alpha

Abstract: Multiple myeloma is caused by abnormal plasma cells that accumulate in the bone marrow and interact with resident cells of the bone microenvironment to drive disease progression and development of an osteolytic bone disease. Bone marrow adipocytes (BMAds) are emerging as having important endocrine functions that can support myeloma cell growth and survival. However, how BMAds respond to infiltrating tumor cells remains poorly understood. Using the C57BL/KaLwRij murine model of myeloma, bone marrow adiposity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
0
56
0
1
Order By: Relevance
“…Obesity is associated with an increase in BMAT. We have previously demonstrated that marrow adipocytes are elevated in the early stages of MM and are supportive of MM growth and survival ( 30 ). To determine whether eliglustat impacts marrow adiposity, tibiae were stained with osmium tetroxide and visualized by micro-CT. Quantitative analysis of regulated BMAT (red area within the red rectangle) revealed a significant increase of regulated BMAT in HFD+MM (MGUS) as compared to the MM group (control); eliglustat treatment did not alter regulated BMAT volume indicating that the effects of eliglustat were not due to changes in adiposity in the BM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is associated with an increase in BMAT. We have previously demonstrated that marrow adipocytes are elevated in the early stages of MM and are supportive of MM growth and survival ( 30 ). To determine whether eliglustat impacts marrow adiposity, tibiae were stained with osmium tetroxide and visualized by micro-CT. Quantitative analysis of regulated BMAT (red area within the red rectangle) revealed a significant increase of regulated BMAT in HFD+MM (MGUS) as compared to the MM group (control); eliglustat treatment did not alter regulated BMAT volume indicating that the effects of eliglustat were not due to changes in adiposity in the BM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stained tibias were embedded in 1% agarose and scanned using a Skyscan 1172 desktop micro‐CT (Bruker) as previously described. ( 31,32 ) The data were reconstructed using Skyscan software NRecon v1.6.9.4 (Bruker). Volumetric analysis was performed using CTAn v1.13.5.1 (Bruker).…”
Section: Methodsmentioning
confidence: 99%
“…Static histomorphometry was performed using the BIOQUANT OSTEO software package (BIOQUANT Image Analysis Corporation, USA) as per manufacturer's instructions and following ASBMR bone histomorphometry guidelines (30) . (31,32) . The data were reconstructed using Skyscan software NRecon v1.6.9.4 (Bruker, Belgium).…”
Section: Accepted Articlementioning
confidence: 99%
“…Adipokines and free fatty acids released by BM adipocytes directly or indirectly interfere with cells of bone remodeling or hematopoiesis (Hardouin et al, 2016). Tumor cells can induce the phosphorylation of hormone-sensitive lipase and activate lipolysis in BMAT, allowing the transfer of fatty acids from adipocytes to tumor cells in AML (Shafat et al, 2017;Tabe et al, 2020), multiple myeloma (Morris et al, 2020), and prostate tumor (Herroon et al, 2019). Importantly, after chemotherapy, marrow necrosis and the loss of myeloid tissue may result in a BMAT expansion (Hwang and Panicek, 2007;Costa and Reagan, 2019), which might create a favorable niche for tumor cells.…”
Section: Bone Marrow Adipose Tissue and Neoplasmsmentioning
confidence: 99%
“…BMAT increases during an early stage of murine myeloma, where marrow adipocytes localize along the tumor-bone interface at later stages of the disease. In addition, myeloma cells downregulate BMAT-derived adiponectin, adjusting the marrow microenvironment to support cancer progression (Morris et al, 2020). Myeloma cells also reprogram adipocytes via the increased methylation of PPARγ and altered adipokine production, which activates osteoclastogenesis and osteolytic lesion formation (Liu et al, 2019).…”
Section: Bone Marrow Adipose Tissue and Neoplasmsmentioning
confidence: 99%